Reflexões sobre os juízos de caráter jurídico e sua possível associação ao conceito de admirabilidade das ciências normativas de Peirce - D'Oliveira, Júlio César (2023)
The projection of the ideal virtues of the ethical being addresses the need for feedback of subsidies aiming at the feasibility of coexistence without dispensing reflections to consent about the meaning of life, a factor always presents in the minds of philosophers. Life in its human context has its idiosyncratic rules that allow evolution and continuity. This plot supports and supports its organization and the establishment of criteria that provide necessary conditions for the best possible way to achieve happiness. Nowadays, it is noted that the systems hitherto considered orthodox, bureaucratic and dogmatic are unwanted, moving to the need for something more fluid and smoother, without legislative complexities and state weight. In this trajectory we will analyze the field of Law in its most bureaucratic way of acting: Judiciary and the elements that orbit around it. To this end, the core of the exposition of the Peircean concept of Normative Sciences, which represents one of the three groups of philosophical sciences, the other two being Phenomenology and Metaphysics, and is subdivided into Aesthetics, Logic and Ethics, will be the main axis. For the presentation of a suggestion for the Brazilian justice system. Going through this path that moves between Peircean and Ibrian philosophies will help us a lot in the analysis of the phenomenal world, according to the cosmology of categories in an observational dimension that allows a cognition closer to reality, aiming to remove veils of fantasy, which cause so much delay in the discovery of truth, the main aim of Philosophy. Representations, which arouse attention and interest, excite responses or suggest interference, and this occurs at the level of reality. Normative Sciences have the necessary attributes to understand the real and provide forecasts and planning. It is not unknown that the History of Philosophy is essential for the formation of the fabric of knowledge, serving as a solid basis for, among others, going through fundamental questions intrinsic to human nature. In view of this, Aesthetics, as a science of the admirable, will help to unveil basic principles of the form of human social life, interesting to the pragmatic method in its highest degree of application, according to Ibrian philosophy. This philosophical architecture, especially Aesthetics and Ethics, will be factored to enable its application in the legal world, ensuring a cohesive and harmonious reasoning as close as possible to an admirable result. It is up to the Normative Sciences, which study the universal laws that characterize phenomena in relation to their ends, to promote their mental consideration according to the dichotomies of what is beautiful, good and true, providing the Law to unveil its objects, which is absolutely imperative for the formulation of clear and immediate convictions, ideas and intuitions. To understand all this theoretical organization, it is necessary to go over other related topics, such as Metaphysics and Phenomenology. From this, we will seek to refine the concept extracted from the feeling of admiration to clarify the notion of this element expressed as an aesthetic pleasure and insert it in the minds that promote legal products, providing greater social satisfaction, something that, nowadays, has been emptied of the métier so peculiar to judicial activities